Cardiovascular Disease Admissions in Medical Wards of a Tertiary Hospital in North - Western Nigeria - Saidu, Dr. Hadiza (Journal of Medical Biomedical and Applied Sciences, 2017)
Introduction: Cardiovascular disease (CVD) is a leading cause of death worldwide and has shown increase in its prevalence since the 19th century. The increase in prevalence was attributable to epidemiologic transition with westernization and changing life style patterns with resultant increase in the risk factors for cardiovascular diseases. This study was carried out to determine the pattern of cardiovascular disease admissions in Murtala Muhammad Specialist hospital, (MMSH) Kano, North â west Nigeria.Methods: Methods: The study was retrospective covering the period from January 2013 to December 2015. Statistical Package for Social Sciences (SPSS) version 19 software was used to analyze data.Results: Out of 4834 patients (males, 2526 and females, 2308) admitted in to the medical wards, 2,119 were recruited in to the study. Stroke (54.6%), congestive cardiac failure (CCF)(26.6%) and hypertension(15.7%) were the most prevalent admitted CVDs.Conclusion: Cardiovascular diseases contributed significantly to medical admissions with the elderly accounting for significant proportion. There is the need for planning to accommodate health problems with emphasis to primary preventive measures for cardiovascular diseases.Key words: Cardiovascular disease, Admissions, North â western Nigeria.